'So I Feel Like I'm Getting It and Then Sometimes I Think OK, No I'm Not': Couple and Family Therapists Learning an Evidence‐Based Practice. Issue 1 (March 2016) - Allan, Robert; Ungar, Michael; Eatough, Virginia
Abstract : This research concerns itself with the experiences of couple and family therapists (CFTs) learning about and using an evidence‐based practice (EBP). The engagement with EBP is growing across many aspects of the mental health and health care systems. The EBP model is now being applied in a broad range of health and human service systems, including mental and behavioural health care, social work, education, and criminal justice (Hunsley, 2007). The dialogue about the role of evidence‐based approaches in the practice of CFT and research literature is also evolving (Sexton et al., 2011; Sprenkle2012 ). Interestingly, while the research delves into what are the best approaches with different populations and presenting issues, little research has explored the experience of CFTs themselves, particularly while learning an EBP. Using a phenomenological approach called interpretive phenomenological analysis (Smith, Flowers & Larkin, 2009), this research explores the experiences of CFTs learning and using an EBP. The paper reports on key issues, challenges, and areas for CFTs, educators, and supervisors. As researchers, educators, administrators, policy makers, and CFTs struggle with what works best with which populations and how best to allocate resources, this research contributes to dialogues about how best to educate and support CFTs, and the complexity of doing research in real‐life settings.